Analysis of People Hours (JO) on the BRS Ship Project and Ship Material Procurement Planning at PT PAL Indonesia Production Management Office Division - Kusumadini, Liana Rahma; Nirawati , Lia (Business and Investment Review, 2025)
Abstract This paper analyzes the efficiency of man hours (JO) in the BRS shipbuilding project as well as material procurement planning at PT PAL Indonesia. The effectiveness of labor and material management is a key factor in the success of maritime projects. This study uses quantitative analysis method to calculate JO realization and supply chain management approach to design procurement strategy. The results show that careful JO planning can improve productivity and cost efficiency, while a structured procurement strategy helps reduce the risk of delays in production. By implementing proper project management, PT PAL Indonesia can optimize resources in the shipbuilding process. Abstrak Tulisan ini menganalisis efisiensi jam orang (JO) dalam proyek pembangunan kapal BRS serta perencanaan pengadaan material di PT PAL Indonesia. Efektivitas pengelolaan tenaga kerja dan material menjadi faktor kunci dalam keberhasilan proyek maritim. Studi ini menggunakan metode analisis kuantitatif untuk menghitung realisasi JO serta pendekatan manajemen rantai pasokan untuk merancang strategi pengadaan. Hasil penelitian menunjukkan bahwa perencanaan JO yang matang dapat meningkatkan produktivitas dan efisiensi biaya, sementara strategi pengadaan yang terstruktur membantu mengurangi risiko keterlambatan dalam produksi. Dengan menerapkan manajemen proyek yang tepat, PT PAL Indonesia dapat mengoptimalkan sumber daya dalam proses pembangunan kapal. Kata kunci: Jam Orang (JO), Manajemen Proyek, Pengadaan Material, Kapal BRS, PT PAL Indonesia.